2014
DOI: 10.1371/journal.pone.0088953
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Involvement in the Disappearance of Steroidogenic Cells from the Corpus Luteum during Luteolysis

Abstract: In mammals, the corpus luteum (CL) is an essential endocrine gland for the establishment and maintenance of pregnancy. If pregnancy is not established, the CL regresses and disappears rapidly from the ovary. A possible explanation for the rapid disappearance of the CL is that luteal cells are transported from the ovary via lymphatic vessels. Here, we report the presence of cells positive for 3β-hydroxysteroid dehydrogenase (3β-HSD), an enzyme involved in progesterone synthesis, in the lumen of lymphatic vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Regarding our observation concerning the existence of lymphatic vessels in the albicans body, we conclude that they could determine the destruction of steroidogenic cells, although this has not yet been fully elucidated (33).…”
Section: Cobec Et Al: Podoplanin In Ovarian Cancermentioning
confidence: 71%
“…Regarding our observation concerning the existence of lymphatic vessels in the albicans body, we conclude that they could determine the destruction of steroidogenic cells, although this has not yet been fully elucidated (33).…”
Section: Cobec Et Al: Podoplanin In Ovarian Cancermentioning
confidence: 71%
“…During the estrous cycle, the CL is developed from the ovulatory follicle and undergoes remarkable growth, differentiation and remodeling . If an oocyte is not fertilized, the CL will regress, with apoptosis of luteal cells and a decline in P4 synthesis . Furthermore, there are three different phases due to the luteal lifespan, namely, the developing, mature and regressing CL .…”
Section: Introductionmentioning
confidence: 99%
“…10 If an oocyte is not fertilized, the CL will regress, with apoptosis of luteal cells and a decline in P4 synthesis. 11,12 Furthermore, there are three different phases due to the luteal lifespan, namely, the developing, mature and regressing CL. 13 Due to the number of ovulation events and the length of cycles, the CL of rodents and primates presents obvious difference including luteal phase length, luteotropins and mechanisms of luteal regression.…”
Section: Introduction Corpus Luteummentioning
confidence: 99%
“…During structural luteolysis, luteal cells are eliminated by apoptosis and phagocytosis by macrophages [ 2 , 3 , 4 ]. We recently found that during structural luteolysis luteal cells flow out of the CL via lymphatic vessels [ 5 ], although the mechanisms regulating the outflow are unclear.…”
mentioning
confidence: 99%
“…The aim of the present study was to validate possibility of the above idea. Since outflow of luteal cells occurs during luteolysis [ 5 ], we hypothesized that luteolytic factors increase MMP expression in luteal cells. To test this hypothesis, we investigated the effects of three factors that are known to induce luteolysis PGF, interferon γ (IFNG) and tumor necrosis factor α (TNF) [ 4 ]) on the mRNA expressions of four MMPs involved in degrading collagen and the basal membrane in cultured luteal cells.…”
mentioning
confidence: 99%